Impact of international nuclear safety conventions on the evolution of Kazakhstan’s legislative framework in the nuclear energy sector - Saipinov, D.R. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article examines the influence of international conventions and nuclear safety standards on the legislative policy of the Republic of Kazakhstan in the field of atomic energy. The relevance of the research is driven by Kazakhstan’s plans to construct a nuclear power plant and the growing need to strengthen national regulatory frameworks in line with global safety requirements. The purpose of the study is to identify the mechanisms through which Kazakhstan’s international obligations under the NPT, the Convention on Nuclear Safety, the Joint Convention and IAEA documents are incorporated into national legislation and shape its development. The scientific and practical significance lies in providing a comprehensive analysis of how international norms affect current legal reforms. The methodology is based on comparative legal analysis of international treaties, the 2021 Environmental Code and the Law “On the Use of Atomic Energy”. The findings demonstrate Kazakhstan’s high level of alignment with international standards, including the improvement of radioactive waste management procedures and the advancement of transboundary environmental assessment. The study contributes to understanding the foundational role of international regimes in national policymaking. Its practical value consists of supporting further enhancement of the legal framework necessary for the implementation of nuclear energy projects.